Constraints of ICT Adoption in Agriculture in Khurda and Bargarh Districts of Odisha - Guru Prasad Satapathy; Sarbani Das; Bijaya Laxmi Sahu; Sidharth Dash; Maitreyee Tripathy (Indian Journal of Extension Education, 2024)
The study was conducted in 2023 in Balipatna and Balianta blocks of Khurda district and in Bijepur and Padampur blocks of Bargarh district of Odisha to determine the constraints affecting farmers using Information Communication Technology in agriculture. The study used purposive sampling for selection of districts and blocks and random sampling procedure for selection of villages and respondent farmers and collected data through personal interviews and focussed group discussion method with 200 respondent farmers. Garrett’s ranking technique was performed to analyse the challenges as perceived by farmers under social, economic and technical dimensions. Lack of knowledge on ICT application on agriculture, lack of financial support from the government and insufficient knowledge on mechanization of access on ICTs platform were important constraints under social, economic and technical dimension respectively in Khurda district. Tendency of following traditional method of information seeking, skeptical image of farmers in front of banking institutions and deficiency in support services are major constraints under social, economic and technical dimensions respectively in Bargarh district. It is important for stakeholders to take the necessary action to eliminate the identified obstacles. It is essential to solve these issues if we want to boost the productivity of farmers in Odisha.